Symptoms of depression are associated with physical inactivity but not modified by gender or the presence of a cardiovascular disease; a cross-sectional study - Achttien, Retze; Wensing, Michel (BMC cardiovascular disorders, 2019)
Depressive symptomatology may act as a barrier to enhance physical activity. This phenomenon is predominantly found in patients with an established cardiovascular disease (CVD) and in female patients. This cross-sectional study investigated (1) the association between symptoms of depression and physical inactivity, and (2) whether this association is different between primary and secondary prevention patients, and between men and women.